Transient receptor potential A1 channels regulate epithelial cell barriers formed by MDCK cells. Issue 10 (3rd May 2016) - Dembla, Sandeep; Hasan, Nouma; Becker, Alexander; Beck, Andreas; Philipp, Stephan Ernst
Abstract : Transient receptor potential A1 channels are well‐known as chemosensors in neuronal cells. However, recent studies also point to non‐neuronal functions in epithelia. Here, we show that TRPA1 channels are expressed in epithelial MDCK II cells and contribute to Ca 2+ influx and whole‐cell currents after stimulation with AITC. Stimulation of TRPA1 channels induced an immediate reduction of the transepithelial resistance of MDCK II cell layers that was blocked by the TRPA1 antagonist HC‐030031. The present data provide strong evidence for a new role of TRPA1 channels in regulating the tightness of epithelial cell barriers. Abstract :